The mediating role technology adoption in the relationship between financial factors and economic well-being in Agricultural context - Wijekoon, Rusitha; Sabri, Mohamad Fazli; Ahmad, Nobaya; Abdul Rahim @ Abdul Wahab, Husniyah (Human Resource Management Academic Research Society, 2022)
Due to the inadequacy of the related research, the key objective of this research is to determine the impact of financial antecedents on growers’ agricultural technology adoption and economic well-being. A cross sectional survey was carried out among Sri Lankan coconut growers who were chosen through the multi stage random sampling procedure. Based on the PLS-SEM results, all the direct associations between financial factors (financial knowledge, financial behaviour), and economic well-being were accepted. Moreover, two variables together explained 87.9% of the variance in economic well-being. The mediating effect of technology adoption between financial knowledge, financial behavior and economic well-being was also revealed significant. The current study is addressed the existing gaps in the field of family economics and management, and understand the impact of financial factors on agricultural technology adoption and economic well-being. Moreover, it guides policy makers in developing policies to improve well-being by improving financial related factors among individuals, particularly in developing countries, in order to reduce the poverty.